2018
DOI: 10.1002/dta.2406
|View full text |Cite
|
Sign up to set email alerts
|

Drug–drug interaction and doping: Effect of non‐prohibited drugs on the urinary excretion profile of methandienone

Abstract: The potential consequences of drug-drug interactions on the excretion profile of the anabolic androgenic steroid methandienone (17β-hydroxy-17α-methylandrosta-1,4-dien-3-one) are discussed. More specifically, we have evaluated by in vitro and in vivo experiments the effects of 7 non-prohibited drugs (fluconazole, ketoconazole, itraconazole, miconazole, fluoxetine, paroxetine, and nefazodone) on the main metabolic pathways of methandienone. These are selected among those most commonly used by the athletes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…22 The hydroxylation of methyltestosterone (MT), testosterone (T), progesterone and other steroids (viz. turinabol, metandienone and fluoxymesterone) on position C6β has been described 23 after incubation with CYP3A4, 2B6, 3A5, 2D6, 2C9 and 2C19. For some steroids, this route (6β-hydroxylation) is the most important in their metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…22 The hydroxylation of methyltestosterone (MT), testosterone (T), progesterone and other steroids (viz. turinabol, metandienone and fluoxymesterone) on position C6β has been described 23 after incubation with CYP3A4, 2B6, 3A5, 2D6, 2C9 and 2C19. For some steroids, this route (6β-hydroxylation) is the most important in their metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Another factor necessitating consideration in the interpretation of sports drug testing analytical data is the co‐administration of permitted drugs potentially affecting the elimination profiles of prohibited substances. Mazzarino et al comprehensively studied the influence of antifungal agents and antidepressants (selective serotonin reuptake inhibitors and serotonin antagonists/reuptake inhibitors) on in vitro and in vivo metabolic reactions and, consequently, the traceability of metandienone metabolites in human urine . Especially the antifungals ketoconazole and miconazole were found to interfere with the phase‐I and phase‐II metabolism of metandienone, potentially negatively affecting the detection window for commonly targeted long‐term metabolites in routine doping controls.…”
Section: Anabolic Agentsmentioning
confidence: 99%
“…Indeed, they can alter the biotransformation and conjugation metabolic reactions also in humans, with effects on the dynamics of the biosynthetic pathways of numerous biologically active substances, including steroids. [6][7][8][9][10][11][12][13][14][15][16][17][18] Different studies reported (i) the ability of ketoconazole to interact with both the 17αhydroxylase and 17,20-lyase activity of cytochrome P450c17, the enzyme that converts pregnenolone to dehydroepiandrosterone and progesterone to androstenedione in the human testes, ovaries, and adrenal glands [6][7][8] ; (ii) the inhibitory effect of several triazole antifungals on the CYP19, responsible for the conversion of testosterone to estradiol, and androstenedione to estrone, due to their structural homology with several aromatase inhibitors, such as letrozole and anastrozole 9,10 ; and (iii) the strong inhibitory effect of antifungals on several hepatic CYP450 isoforms (e.g., CYP3A4) and uridine 5 0 -diphosphoglucuronosyltransferases (UGTs) involved in the biotransformation pathways of steroids. [11][12][13][14][15][16][17][18] In the doping control field, the alteration of the natural fluctuation of several endogenous steroids (currently: testosterone [T],…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18] Different studies reported (i) the ability of ketoconazole to interact with both the 17αhydroxylase and 17,20-lyase activity of cytochrome P450c17, the enzyme that converts pregnenolone to dehydroepiandrosterone and progesterone to androstenedione in the human testes, ovaries, and adrenal glands [6][7][8] ; (ii) the inhibitory effect of several triazole antifungals on the CYP19, responsible for the conversion of testosterone to estradiol, and androstenedione to estrone, due to their structural homology with several aromatase inhibitors, such as letrozole and anastrozole 9,10 ; and (iii) the strong inhibitory effect of antifungals on several hepatic CYP450 isoforms (e.g., CYP3A4) and uridine 5 0 -diphosphoglucuronosyltransferases (UGTs) involved in the biotransformation pathways of steroids. [11][12][13][14][15][16][17][18] In the doping control field, the alteration of the natural fluctuation of several endogenous steroids (currently: testosterone [T],…”
Section: Introductionmentioning
confidence: 99%